Performance and brain activity during the Wisconsin Card Sorting Test in adolescents with obsessive–compulsive disorder and adolescents with weight-restored anorexia nervosa. - Bohon, Cara; Weinbach, Noam; Lock, James (European Child & Adolescent Psychiatry, 2020)
Anorexia nervosa (AN) and obsessive–compulsive disorder (OCD) both show a peak age of onset during adolescence and share a number of phenotypic features, such as rigid rule-bound behavior and perseverative thinking. There is evidence of difficulties with set shifting or task switching in adults with each disorder, but evidence in adolescents is limited. Furthermore, no studies have previously directly compared AN and OCD on this cognitive process or examined comparative neural correlates. This study provides exploratory analyses to address this gap by measuring brain activity with functional magnetic resonance imaging (fMRI) during a computerized version of the Wisconsin Card Sorting Test (WCST) in female adolescents with weight-restored AN (WR-AN) (n = 14), OCD (n = 11), and healthy controls (n = 24). Results revealed greater perseverative errors in the OCD group than healthy controls and WR-AN, but no difference between WR-AN and healthy controls. Greater activity in the right front pole, inferior frontal gyrus, and middle frontal gyrus during the task (compared to a control matching task) was associated with more perseverative errors in the OCD group, but not healthy controls. The correlation between perseverative errors and brain response to the task in the WR–AN group was not different from either comparison group. These findings propose a hypothesis that behavioral similarities between OCD and AN, as well as difficulties with set shifting in adults with AN, are driven by obsessive–compulsive features present in AN rather than a shared underlying neurocognitive signature. This notion should be tested in larger samples in future studies.